Influence of strategic points in the dispersion of Aedes aegypti in infested areas - Gerson Laurindo Barbosa; Mariana de Oliveira Lage; Valmir Roberto Andrade; Antônio Henrique Alves Gomes; Jose Alberto Quintanilha; Francisco Chiaravalloti-Neto (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To evaluate whether sites with large amount of potential breeding sites for immature forms of Aedes aegypti, called strategic points, influence in the active vector's dispersion into properties in their surroundings. METHODS: We selected four areas in the municipality of Campinas, three of them with strategic points classified as high, moderate, and low risk according to infestation and a control area, without strategic points. Between October 2015 and September 2016, we monthly installed oviposition traps and evaluated the infestation by Ae. aegypti in all properties of each selected area. To verify if there was vector dispersion from each strategic point, based on its location, we investigated the formation of clusters with excess of eggs or larvae or pupae containers, using the Gi spatial statistics. RESULTS: The amount of eggs collected in the ovitraps and the number of positive containers for Ae. aegypti did not show clusters of high values concerning its distance from the strategic point. Both presented random distribution not spatially associated with the positioning of strategic points in the area. CONCLUSIONS: Strategic points are not confirmed as responsible for the vector's dispersion for properties in their surroundings. We highlight the importance of reviewing the current strategy of the vector control program in Brazil, seeking a balance from the technical, operational, and economic point of view, without disregarding the role of strategic points as major producers of mosquitoes and their importance in the dissemination of arboviruses in periods of transmission.